ASSOCIATION BETWEEN CD4 CELL COUNT AND OCULAR SYPHILIS IN HIV-INFECTED POPULATION: A CROSS-SECTIONAL ANALYSIS - Evani, Saphira; Pramita, Ida Ayu Ary; Juliari, I Gusti Ayu Made (E-Jurnal Medika Udayana, 2025)
Ocular syphilis (OS) manifestations mimic other conditions, often leading to HIV diagnosis. The CD4 cell count is a reliable indicator of a HIV patient's immune system condition. This cross-sectional analysis seeks to explore the relationship between CD4 cell counts and the prevalence of OS in individuals living with HIV. A cross-sectional study was conducted in the Ophthalmology Department, analyzing data from 21 HIV-positive OS patients registered at the VCT Clinic of Prof. dr. I.G.N.G. Ngoerah General Hospital between 2018 and 2023. The research encompassed 18 male participants (85.71%), alongside 3 female participants (14.29%). The average age was 35.76 ± 10.70 years. The most common ocular manifestation of syphilis was panuveitis with bilateral involvement. There was no statistically significant association between CD4 cell count and ocular manifestations of syphilis and visual acuity in HIV-positive patients. Despite the lack of a connection between the CD4 cell count in HIV-positive patients, it is recommended to perform HIV testing for all individuals diagnosed with syphilis, given the frequent coexistence of these infections. Keywords: Ocular syphilis, CD4 cell count, uveitis